APPLICATION OF CLUSTERING GROUPS IN DETERMINING LAND SUITABILITY - Angga Pratama; Salamah Salamah; Mutammimul Ula; Nadya Hayana (Multica Science and Technology, 2021)
The problem of the suitability of planting land for planting types of plants is still a lot of unresolved farmers. land at the beginning of land selection is very decisive. This is to determine whether the land is productive or not. in the future is the result that farmers will experience considerable losses if this is not estimated, therefore a model is needed to know and estimate accurately whether the land or land is suitable for planting crops or not. The purpose of this study is that farmers do not experience losses and losses on land when planting crops on available land. So that it can improve the quality of food in Aceh and can improve the welfare of farmers. The result of the research is that it can be found a Clustering model or grouping of plant stock types using the k-medoid model, finally the application of this clustering model is able to provide a solution for the Office. Based on calculations using the K-Medoids method obtained for land compliance in North Aceh Regency is Corn with an adjustment of 53.6%, Peanuts 17.9%, Soybeans 14.3%, Bulbs 10.7% and the suitability for rice is 3 ,6%.